Pengaruh Kebijakan Kepala Sekolah Terhadap Prestasi Belajar Siswa di Madrasah Tsanawiyah Negeri 1 Kabupaten Bolaang Mongondow Timur - Mamonto, Yusril Eka Putra; Lisdawati Muda; Putriani L Maliki (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the extent to which school principals’ policies influence student achievement at MTs Negeri 1 Bolaang Mongondow Timur. The role of the principal as the leader of an educational institution is not only limited to administrative functions but also extends to strategic decision-making that directly affects the learning process and students’ academic outcomes. Therefore, this research seeks to provide empirical evidence regarding the relationship between principals’ policies and student learning achievement. The research employed a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to students, documentation of academic records, and direct observation within the school environment. The population of this study comprised all students at MTs Negeri 1 Bolaang Mongondow Timur. The sample was determined using a purposive sampling technique to ensure that the respondents met the research criteria. Data analysis was conducted using Pearson’s correlation to measure the strength of the relationship between variables and the coefficient of determination to determine the extent of the principal’s policy contribution to student achievement. The findings revealed a significant and positive influence of the principal’s policies on student academic performance. The Pearson correlation coefficient obtained was 0.877, indicating a very strong relationship. Furthermore, the coefficient of determination of 77% showed that the principal’s policies contributed substantially to students’ academic achievement, while the remaining 23% was influenced by other factors such as family environment, individual motivation, and supporting infrastructure. In conclusion, the study highlights that school principals’ policies play an essential role in creating a conducive learning environment and supporting the improvement of student achievement. The implications of this research emphasize the importance of principals formulating adaptive, participatory, and student-oriented policies to enhance the quality of education at MTs Negeri 1 Bolaang Mongondow Timur.